THE MAIN PROSPECTS AND CONSEQUENCES OF UKRAINE’S ACCESSION TO THE INTERNATIONAL TRADE ORGANIZATION AND THE EUROPEAN UNION FOR THE TRANSPORT COMPLEX - Nykyforuk, O. I. (Science and Transport Progress, 2008)
The prospects and consequences of integration ofUkraineto the WTO and the EU for transport complex have been considered. The SWOT-analysis of economic after-effects after such an integration has been performed.